2023
DOI: 10.1002/aoc.7051
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of NO adsorptive selectivity by the embedding of Rh in MOF‐177 as carrier

Abstract: In this paper, MOF-177 was embedded with Rh for the improvement of NO adsorptive selectivity at room temperature. The results showed that the experimental NO saturated adsorption capacity of MOF-177 was very limited value of 1.35 mLÁg À1 with a negligible selectivity, but the embedded 3 wt % Rh/MOF-177 improved it to 16 mLÁg À1 with higher maximal selectivity of NO to CO 2 (352) and to O 2 (600) under low partial pressure. In the simulated mixture gas, the adsorption capacity of NO atmosphere was about 9-18 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…With respect to NO adsorption and separation performance, Hu et al 14,15 first systematically compared and verified the potential of bimetallic NiCo-MOF-74 and MnCo-MOF-74 for NO separation and adsorption performance in mixed atmosphere by experiments, and they also demonstrated that the separation and adsorption performance of MOF-177 for NO could be substantially improved by the load of metal nanoparticles. 16 The accessible -NH 2 functional groups in MOFs materials can also exhibit adsorptive storage property for NO, but the adsorptive separation property involving NO is currently absent. Lowe et al 17 constructed MOFs based on TDPAT ligands, and their study showed that the containing secondary amine functional groups on the ligands can form NONOate structures with NO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to NO adsorption and separation performance, Hu et al 14,15 first systematically compared and verified the potential of bimetallic NiCo-MOF-74 and MnCo-MOF-74 for NO separation and adsorption performance in mixed atmosphere by experiments, and they also demonstrated that the separation and adsorption performance of MOF-177 for NO could be substantially improved by the load of metal nanoparticles. 16 The accessible -NH 2 functional groups in MOFs materials can also exhibit adsorptive storage property for NO, but the adsorptive separation property involving NO is currently absent. Lowe et al 17 constructed MOFs based on TDPAT ligands, and their study showed that the containing secondary amine functional groups on the ligands can form NONOate structures with NO.…”
Section: Introductionmentioning
confidence: 99%
“…Their strong binding ability for NO has been well confirmed. With respect to NO adsorption and separation performance, Hu et al 14,15 first systematically compared and verified the potential of bimetallic NiCo‐MOF‐74 and MnCo‐MOF‐74 for NO separation and adsorption performance in mixed atmosphere by experiments, and they also demonstrated that the separation and adsorption performance of MOF‐177 for NO could be substantially improved by the load of metal nanoparticles 16 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, they also post-functionalized MOF-177 by loading 3 wt% Rh nanoparticles to improve the NO adsorption selectivity at room temperature up to 352 for NO/CO 2 and up to 600 for NO/O 2 in the low-pressure range, and the breakthrough in mixed atmosphere adsorption selectivity of NO/CO 2 and NO/O 2 can also reach up to 18. 20 Their results showed that referencing the second metal centre can improve the NO adsorption selectivity of MOFs materials. Therefore, in this work, we continue to introduce the second metal centre of Mn component into Co-MOF-74 to further research on MOF material improvements on the NO adsorption selectivity and expect to obtain more expanded research experience of MOF materials to improve NO adsorption selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the NO adsorption capacity of bimetallic Ni 0.37 Co 0.63 ‐MOF‐74 was 16.3% higher than that of monometallic Co‐MOF‐74 at room temperature, and the selectivity of its Ideal Adsorption Solution Theory (IAST) adsorption in the low‐pressure region reached 710 for NO/CO 2 , and a high NO/CO 2 adsorption selectivity of 13.8 was also obtained in a mixed atmosphere breakthrough experiment. In addition, they also post‐functionalized MOF‐177 by loading 3 wt% Rh nanoparticles to improve the NO adsorption selectivity at room temperature up to 352 for NO/CO 2 and up to 600 for NO/O 2 in the low‐pressure range, and the breakthrough in mixed atmosphere adsorption selectivity of NO/CO 2 and NO/O 2 can also reach up to 18 20 . Their results showed that referencing the second metal centre can improve the NO adsorption selectivity of MOFs materials.…”
Section: Introductionmentioning
confidence: 99%